Improving the Detection of Individuals at Clinical Risk for Psychosis in the Community, Primary and Secondary Care: An Integrated Evidence-Based Approach - Fusar-Poli, Paolo; Sullivan, Sarah A.; Shah, Jai L.; Uhlhaas, Peter J. (Frontiers in Psychiatry, 2019)
Background The first rate-limiting step for improving outcomes of psychosis through preventive interventions in people at Clinical High Risk for Psychosis (CHR-P) is the ability to accurately detect individuals who are at risk for the development of this disorder. Currently, this detection power is poor. Methods Conceptual and nonsystematic review of the literature, focusing on the work conducted by leading research teams in the field. The results will be structured in the following sections: understanding the CHR-P assessment, validity of the CHR-P as a universal risk state for psychosis, improving the detection of at-risk individuals in secondary mental health care, in primary care, and in the community. Results CHR-P instruments can provide adequate prognostic accuracy for the prediction of psychosis provided they are employed in samples who have undergone risk enrichment during recruitment. This substantially limits their detection power in real-world settings. Furthermore, there is evidence that not all cases of psychosis onset occur via a CHR-P stage. A transdiagnostic individualized risk calculator could be used to automatically screen secondary mental health care medical notes to detect those at risk of psychosis and refer them to standard CHR-P assessment. Similar risk estimation tools for use in primary care are under development and promise to boost the detection of patients at risk in this setting. To improve the detection of young people who may be at risk of psychosis in the community it is necessary to adopt digital and sequential screening approaches. These solutions are based on recent scientific evidence and have international potential for implementation internationally. Conclusions The best strategy to improve the detection of patients at risk for psychosis is to implement a clinical research program that integrates different but complementary detection approaches across community, primary and secondary care. These solutions are based on recent scientific advancements in the development of risk estimation tools and e-Health approaches and have the potential to be applied across different clinical settings.